The Development of Focusky as Learning Media on Recount Text to Improve Students' Vocabulary Mastery - Natra, Bima; Pahmi, Pahmi; Syahfutra, Wandi (FKIP - Universitas Riau, 2024)
This study delves into the development and implementation of an application-based learning media called